Footwear Alters Lower Extremity Coordination Variability. Issue 5 (October 2019) - Romer, Braden H.; Weimar, Wendi; Fox, John
Footwear has been shown to have a significant effect on numerous kinematic and kinetic variables during walking and running. While footwear mass is an indisputably important influence on gait patterns, we suspected that the amount of outsole material on most footwear would likely diminish or delay the integration of tactile feedback in motor control strategies during gait. Thus, we designed this study to investigate the influence of footwear and augmented tactile feedback on lower extremity coordination patterns during walking. A secondary purpose of the study was to examine gender differences in response to altered footwear conditions. Forty-eight participants (24 male and 24 females) walked during four standardized footwear conditions (barefoot, shod, barefoot with augmented tactile feedback, and shod with augmented tactile feedback), and we collected three-dimensional kinematic data and calculated continuous relative phase values for two adjacent lower extremity joints to determine interjoint coordination patterns. We used deviation phase and the mean of the continuous relative phase to compare motor coordination patterns across conditions. We found significant footwear and gender effects for spatiotemporal variables but only significant footwear effects for motor coordination patterns. Females displayed a significantly higher cadence and shorter height-normalized stride length as compared to males. Participants displayed significantly greater thigh-shank coordination variability in the shod, as compared to the unshod, conditions. Thus, footwear results in a diminished or delayed tactile feedback that alters neuromuscular control strategies during walking.